Revitalizing the Epigenome of Adult Jaw Periosteal Cells: Enhancing Diversity in iPSC-Derived Mesenchymal Stem Cells (iMSCs) - Felix Umrath; Valerie Wendt; Gilles Gasparoni; Yasser Narknava; Jörn Walter; Bernd Lethaus; Josefin Weber; Victor Carriel; Meltem Avci-Adali; Dorothea Alexander (Cells)
Induced pluripotent stem cells (iPSCs) are rapidly emerging as a transformative resource in regenerative medicine. In a previous study, our laboratory achieved a significant milestone by successfully reprograming jaw periosteal cells (JPCs) into iPSCs, which were then differentiated into iPSC-derived mesenchymal stem cells (iMSCs). Using an optimized protocol, we generated iMSCs with a remarkable osteogenic potential while exhibiting lower expression levels of the senescence markers p16 and p21 compared to the original JPCs. This study aimed to explore the epigenetic landscape by comparing the DNA methylation and transcription profiles of iMSCs with their JPC precursors, seeking to uncover key differences. Additionally, this analysis provided an opportunity for us to investigate the potential rejuvenation effects associated with cellular reprogramming. To assess the safety of the generated cells, we evaluated their ability to form teratomas through subcutaneous injection into immunodeficient mice. Our findings revealed that, while the methylation profile of iMSCs closely mirrored that of JPCs, distinct iMSC-specific methylation patterns were evident. Strikingly, the application of DNA methylation (DNAm) clocks for biological age estimation showed a dramatic reduction in DNAm age to approximately zero in iPSCs—a rejuvenation effect that persisted in the derived iMSCs. This profound reset in biological age, together with our transcriptome data, indicate that iMSCs could possess an enhanced regenerative potential compared to adult MSCs. Future in vivo studies should validate this hypothesis.